2005
DOI: 10.1136/pgmj.2004.030817
|View full text |Cite
|
Sign up to set email alerts
|

Change of nitric oxide in experimental colitis and its inhibition by melatonin in vivo and in vitro

Abstract: Aim: To investigate the change of nitric oxide (NO) in rat colitis and its inhibition by melatonin in vivo and in vitro. Methods: In vivo, rat colitis was established intracolonically with trinitrobenzenesulphonic acid (TNBS) and ethanol. The animals were randomised into five groups: control group, model group, melatonin group (2.5, 5.0, 10.0 mg/kg), and treated intracolonically with saline, saline and melatonin respectively (once a day, from day 7 after colitis was established to day 28). After the end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 42 publications
5
23
0
Order By: Relevance
“…Mei and co-workers showed that colon inflammation between days 7 and 28 was associated with increased production of NO, and melatonin treatment suppressed the increase of NO; thus the extent of colonic inflammation was inhibited and colon mucosa injury was prevented [30]. These results are compatible with our study.…”
Section: Tnbs-induced Colitis Is a Hapten-induced Model Of Chronicsupporting
confidence: 95%
See 2 more Smart Citations
“…Mei and co-workers showed that colon inflammation between days 7 and 28 was associated with increased production of NO, and melatonin treatment suppressed the increase of NO; thus the extent of colonic inflammation was inhibited and colon mucosa injury was prevented [30]. These results are compatible with our study.…”
Section: Tnbs-induced Colitis Is a Hapten-induced Model Of Chronicsupporting
confidence: 95%
“…For this reason, MPO activity is expected to be high in colon. In our study, MPO activity increased in colitis groups, consistent with previous studies [24,25,[28][29][30][31], and MPO levels were slightly decreased in treated groups, although this decrease was not statistically significant.…”
Section: Tnbs-induced Colitis Is a Hapten-induced Model Of Chronicsupporting
confidence: 93%
See 1 more Smart Citation
“…Both intracolonic melatonin gel formulation and IP administration of melatonin decreased the levels of NOx in colon cells, and it is known that melatonin administration inhibits NOx levels due to its antioxidant properties. Our results showed similarity with the results of previously conducted studies (Mei et al, 2005).…”
Section: In Vivo Studiessupporting
confidence: 83%
“…In studies evaluating the antioxidant efficacy, melatonin with an isotonic saline solution has been administered either intracolonically or through the IP route (Cuzzocrea et al, 2001;Mei et al, 2005;Marquez et al, 2006;Necefli et al, 2006;Nosál'ova et al, 2007). To our knowledge, no in vitro or in vivo intracolonic formulation study has been performed with melatonin.…”
Section: Introductionmentioning
confidence: 99%